1988
DOI: 10.1143/jjap.27.l1803
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Si-H2 Bond Density and Electron Drift Mobility in a-Si:H Films Prepared by Photochemical Vapor Deposition

Abstract: We study black holes in AdS-like spacetimes, with the horizon given by an arbitrary positive curvature Einstein metric. A criterion for classical instability of such black holes is found in the large and small black hole limits. Examples of large unstable black holes have a Böhm metric as the horizon. These, classically unstable, large black holes are locally thermodynamically stable. The gravitational instability has a dual description, for example by using the AdS 7 × S 4 version of the AdS/CFT correspondenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It has already been reported that an increase in Pg results in the change of hydrogen configuration and fewer band-tail states [3].…”
Section: Electron Drift Mobility (Pd) Itime-o-flight I Imentioning
confidence: 95%
“…It has already been reported that an increase in Pg results in the change of hydrogen configuration and fewer band-tail states [3].…”
Section: Electron Drift Mobility (Pd) Itime-o-flight I Imentioning
confidence: 95%